Bi-polymeric structured system (xanthan gum-carboxymethyl cellulose) for developing instant powder with the ability to suspend flixweed seeds in beverages: Effect of pH and sweetener type - Sara Naji-Tabasi; Bahareh Emadzadeh; Seyedeh Fatemeh Mousavi; Saeedeh Shahbazizadeh; Zahra Damavandi (Heliyon)
Creating innovation in the production of beverage products has always been one of the goals of this industry. This investigation studied the fabrication of an instant biopolymeric structured powder to suspend flixweed seeds in a beverage. A mixture of carboxymethyl cellulose (CMC) and xanthan (XG) hydrocolloids in different ratios (CMC at 0.17–0.20 and xanthan XG at 0–0.03) and pH (4.0, 6.5, and 9.0) with sucrose sugar were used to create the instant structured system. Then, the best-structured system in neutral pH was studied along with different sweetener (sucrose, stevia and xylitol). The suspending environment had shear thinning behavior. The viscosity and yield stress of the samples increased by increasing xanthan concentration. pH of the environment had no significant effect on the rheological properties of the solutions (P > 0.05). However, it affected the formation time of the suspending system. The highest percentage of stable suspended seeds and the lowest fractal dimension change during storage time confirmed the samples containing 0.17 % CMC-0.03 % XG had the highest stability. The sensory results also confirmed that increasing the level of XG increased appearance attractiveness score. The low-calorie sweeteners significantly affected the rheological behavior and stability of the suspension system (p < 0.05). The shortest formation time of the structured system was observed in the presence of sucrose. The xylitol samples had the lowest stability and overall acceptance. The results of this study confirm the suitability of the CMC-XG suspending system to be applied for the rapid suspension of various particles.